Oxidation-resistant Al-Mg high-strength die-casting alloy

JP2024514616A5Inactive Publication Date: 2025-02-19RIOTINTO ALCAN INT LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023562873
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-14
Filing Date
2022-04-01
Publication Date
2025-02-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The automotive industry requires aluminum die casting alloys that do not require heat treatment to achieve good mechanical properties, as existing Al-Mg alloys suffer from oxidation and Mg loss during casting, and the use of beryllium poses health risks.

Method used

Development of beryllium-free Al-Mg casting alloys containing Ca or Sr to reduce oxidation and Mg loss, with compositions including Mg 1.0-17.0%, Fe 0.5-1.8%, and Ca 0.003-6.0% or Sr 0.003-2.5%, which can be used in high pressure vacuum die casting without post-casting heat treatment.

Benefits of technology

The alloys exhibit improved mechanical properties, reduced dross formation, and enhanced die seizure resistance, achieving tensile strength of at least 200 MPa, yield strength of at least 100 MPa, and elongation of at least 7% in the as-cast condition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present disclosure relates to a beryllium-free casting alloy suitable for casting operations. The casting alloy includes, in weight percent, one of Mg (about 1.0 to about 17.0), Fe (about 0.5 to about 1.8), Ca (about 0.003 to about 6.0) or Sr (about 0.003 to about 2.5), optionally a grain refiner, and the balance aluminum and unavoidable impurities. The casting alloy can be used in a method for producing aluminum cast products to reduce Mg loss and / or dross formation during the casting operation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 63 / 174,796, filed April 14, 2020, the entire contents of which are incorporated herein by reference.

[0002] The present disclosure relates to Al-Mg casting alloys suitable for casting operations such as high pressure vacuum die-casting operations. [Background technology]

[0003] The demand for structural die cast parts in the automotive industry continues to increase. Most of the existing alloys require heat treatment to produce products with good mechanical properties. Therefore, alloys that do not require heat treatment are required to reduce the manufacturing costs of structural die cast parts.

[0004] Al-Mg die casting alloys have attracted much interest due to their excellent mechanical properties in the as-cast state. To obtain sufficient solid solution strengthening, Al-Mg alloys are produced with high additions of Mg (>3%). However, due to the strong affinity of Mg with oxygen, Al-Mg alloys undergo problematic oxidation that can result in significant dross formation and loss of Mg from the melt. Beryllium can be used to minimize oxidation because it forms a protective BeO layer at the air-metal interface that prevents further oxidation of Mg. However, the use of Be poses health risks to operators who inhale or come into contact with Be dust.

[0005] Therefore, the aluminum die casting market is looking for a replacement for Be in Al-Mg alloys that offers similar oxidation protection but without the associated health risks. There is also a need to provide alloys that exhibit improved properties during the casting operation, such as die soldering resistance. There is also a need to provide aluminum cast products that exhibit improved mechanical properties in the as-cast condition (F temper). Summary of the Invention

[0006] The present disclosure provides beryllium-free casting alloys. The casting alloys of the present disclosure include Ca or Sr. In some embodiments, the casting alloys exhibit reduced Mg loss and / or reduced dross formation during casting operations. In some embodiments, the casting alloys also exhibit improved die seizure resistance during casting operations. In some embodiments, aluminum cast products made from the casting aluminum alloys exhibit improved mechanical properties even in the as-cast condition.

[0007] According to a first aspect, the present disclosure provides a composition comprising, in weight percent: Mg about 1.0~about 17.0; Fe approx. 0.5 to approx. 1.8; one of Ca about 0.003 to about 6.0 or Sr about 0.003 to about 2.5; and Residual amounts of aluminum and unavoidable impurities, wherein the casting alloy does not include Be as an alloying element.

[0008] In one embodiment, the cast alloy further comprises a grain refiner. In another embodiment, it further comprises Ca. In yet another embodiment, the cast alloy comprises from about 0.01 to about 0.3 weight percent Ca. In yet another embodiment, the cast alloy comprises from about 3.0 to about 8.0 weight percent Mg. In yet another embodiment, the cast alloy comprises from about 4.0 to about 6.0 weight percent Mg. In yet another embodiment, the cast alloy comprises from about 0.8 to about 1.8 weight percent Fe.

[0009] According to a second aspect, the present disclosure provides an aluminum casting product comprising a casting alloy as described herein. In some embodiments, the cast aluminum is a structural automotive component. In additional embodiments, the aluminum casting product has at least one of the following properties: a tensile strength of at least about 200 MPa, a yield strength of at least about 100 MPa, an elongation of at least about 7%, and / or a VDA bend angle of at least about 30°. In additional embodiments, the aluminum casting product comprises Al4Ca. In some further embodiments, the aluminum casting product comprises Al4Ca. 13 Fe4 phase, Al3Mg2 phase, and Al4Ca. In some additional embodiments, the aluminum cast product has Al4Ca bonded with the Al3Mg2 phase. In yet additional embodiments, the aluminum cast product has AlMgCa phases at grain boundaries.

[0010] According to a third aspect, the present disclosure provides a method of producing an aluminum cast product, the method comprising casting the cast aluminum alloy described herein in a mold. In one embodiment, the method further comprises subjecting the cast aluminum alloy to high pressure vacuum die casting. In yet another embodiment, the method does not include a post-casting heat treatment step.

[0011] According to a third aspect, the present disclosure provides an aluminum casting product obtainable or obtained by the methods described herein. In some embodiments, the cast aluminum is a structural automotive component. In additional embodiments, the aluminum casting product has at least one of the following properties: a tensile strength of at least about 200 MPa, a yield strength of at least about 100 MPa, an elongation of at least about 7%, and / or a VDA bend angle of at least about 30°. In additional embodiments, the aluminum casting product comprises Al4Ca. In some further embodiments, the aluminum casting product comprises Al4Ca. 13Fe4 phase, Al3Mg2 phase, and Al4Ca. In some additional embodiments, the aluminum cast product has Al4Ca bonded with the Al3Mg2 phase. In yet additional embodiments, the aluminum cast product has an AlMgCa phase at the grain boundaries.

[0012] According to a fourth aspect, the present disclosure provides a method for limiting Mg loss and dross formation during a casting operation of an aluminum product as compared to a control aluminum product, the method comprising adding one of about 0.003 to about 6.0 Ca or about 0.003 to about 2.5 Sr to a first aluminum alloy to obtain a casting alloy intended to be cast, the first aluminum alloy comprising, in weight percent: Mg about 1.0~about 17.0; Fe about 0.5 to about 1.8; and Residual amounts of aluminum and unavoidable impurities, and the first aluminum alloy and the cast alloy do not contain Be as an alloying element.

[0013] In some embodiments, the method further comprises melting the casting alloy to obtain a molten casting alloy. In one embodiment, the first aluminum alloy further comprises a grain refiner. In some additional embodiments, the method can be used to reduce Mg loss to less than about 12 weight percent when the molten casting alloy is held for at least 6 hours. In some further embodiments, the method can be used to reduce dross formation to less than about 7 weight percent when the molten casting alloy is held for at least 6 hours. In some embodiments, the method further comprises casting the molten casting alloy to obtain a cast aluminum alloy. In yet additional embodiments, the method further comprises subjecting the cast aluminum alloy to high pressure vacuum die casting. In some embodiments, the method does not include a post-casting heat treatment step. In some additional embodiments, the cast aluminum alloy comprises Ca. In still further embodiments, the cast aluminum alloy comprises about 0.01 to about 0.3 Ca. In additional embodiments, the first aluminum alloy comprises about 3.0 to about 8.0 Mg. In further embodiments, the first aluminum alloy comprises about 4.0 to about 6.0 Mg. In yet another embodiment, the first aluminum alloy includes from about 0.8 to about 1.8 Fe.

[0014] Having generally described the nature of the present invention, reference is now made to the accompanying drawings, in which preferred embodiments thereof are illustrated. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 shows the experimental procedure used in the examples. [Diagram 2] Figure 2A shows a photograph of the HPVDC plate used in the examples. The dashed lines indicate the sections used in the tensile tests presented in the examples. Figure 2B shows a diagram of the dimensions of the ASTM B557 tensile test specimen used in the examples. [Diagram 3] FIG. 3 shows photographs of the change in the molten surface during the course of the air exposure oxidation test (from left to right, after skimming, 1 hour hold, 2 hour hold, or 20 hour hold). [Figure 4-1] Figure 4A shows a photograph of the morphology of the solid dross. Figure 4B shows an electron microscope image of the dross, showing the energy dispersive X-ray analysis (EDX)-1 and EDX-2 particles. The scale bar is 20 μm. [Figure 4-2] Figure 4C shows the EDX-1 results from Figure 4B, and Figure 4D shows the EDX-2 results from Figure 4B. [Diagram 5] Figure 5A shows the weight percent of Mg in the base alloy (Ca, Sr, and / or combinations of Ca and Sr, stapled lines) over the course of hold times from 0 to 6 hours in alloys containing 100 ppm Ca (■), 1000 ppm Ca (▲), 100 ppm Sr (×), or 1000 ppm Sr (●). Figure 5B shows the percent Mg loss in the base alloy (Ca, Sr, and / or combinations of Ca and Sr) after a total hold time of 6 hours in alloys containing 100 ppm Ca, 1000 ppm Ca, 100 ppm Sr, or 1000 ppm Sr. [Figure 6] FIG. 6 shows photographs of the typical appearance of molten Al-1.5Fe-5Mg base alloys containing no additives, only Ca, only Sr, and a combination of Ca and Sr after a holding time of 2 hours at 770° C. [Figure 7] FIG. 7 shows the total dross formation (weight percent) for the base Al-1.5Fe-5Mg alloy, alloys with only Ca added, alloys with only Sr added, or alloys with a combination of Ca and Sr added, after a total holding time of 6 hours. [Figure 8] The mechanical properties of the base Al-1.5Fe-5Mg alloy and the Ca-added (0.1) alloy are compared in Figure 8. The results are shown as tensile strength (left bar, MPa), yield strength (middle bar, MPa), elongation index (left bar, %), and quality index (■, MPa) for the two alloys compared. [Figure 9]Figure 9 compares the mechanical properties of Comparative Alloy 1, Comparative Alloy 2 (containing Be), and the Al-1.5Fe-5Mg0.1Ca alloy. Results are shown as tensile strength (left bar, MPa), yield strength (middle bar, MPa), elongation index (left bar, %), and quality index (■, MPa) for the three alloys compared. [Figure 10] FIG. 10A shows a representative optical image of the base Al-1.5Fe-5Mg alloy. The arrows point to the porous parts in the material. The scale bar is 100 μm. FIG. 10B shows a representative optical image of the Al-1.5Fe-5Mg0.1Ca alloy. The scale bar is 100 μm. FIG. 10C shows a representative optical image of the base Al-1.5Fe-5Mg alloy. The scale bar is 20 μm. FIG. 10D shows a representative optical image of the Al-1.5Fe-5Mg0.1Ca alloy. The scale bar is 20 μm. [Figure 11] FIG. 11A shows a scanning electron microscope (SEM) image, EDX, and electron backscatter diffraction (EBSD) of the Al13Fe4 phase found in the Al-1.5Fe-5Mg0.1Ca alloy. FIG. 11B shows a scanning electron microscope (SEM) image and EDX of the Al3Mg2 phase found in the Al-1.5Fe-5Mg0.1Ca alloy. FIG. 11C shows a scanning electron microscope (SEM) image, EDX, and electron backscatter diffraction (EBSD) of the Al4Ca component found in the Al-1.5Fe-5Mg0.1Ca alloy. FIG. 11D shows a scanning electron microscope (SEM) image and EDX mapping of the Al-Mg-Ca phase found in the Al-1.5Fe-5Mg0.1Ca alloy. [Figure 12] FIG. 12 provides results showing the effect of Mg on the yield strength of the alloy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Aluminum alloys offer an attractive solution to meet the lightweighting goals in the automotive industry to improve fuel economy and reduce CO2 emissions. High pressure vacuum die casting (HPVDC) is widely used for the production of aluminum structural components as a fast and economical near net shape manufacturing method. Alloys for structural die castings typically require good flow and die seizure resistance, high mechanical properties, and sufficient corrosion resistance. Key challenges addressed by the industry are die seizure, blistering during solution treatment, and the need to combine strength and ductility. From a broad cost and quality standpoint, well-engineered aluminum alloys in tempers F and T5 are preferred.

[0017] In Al-Mg casting alloys, Be is often used to limit or prevent oxidation. However, in the present disclosure, we have sought to replace Be in Al-Mg casting alloys intended for use in casting operations. Surprisingly, it has been found that the addition of Ca or Sr to Al-Mg casting alloys not only limits the oxidation of the alloy during casting operations, but also results in cast products exhibiting improved mechanical properties.

[0018] The cast aluminum alloys of the present disclosure include either Ca or Sr. In some embodiments, the cast aluminum alloy does not include a combination of Ca and Sr. As indicated above, Ca and Sr limit the oxidation of the alloy and, in some embodiments, improve the casting conditions. When the cast aluminum alloy is used to produce a cast product, in some embodiments, it can also improve one or more mechanical properties of the cast product (in some embodiments, in its as-cast state).

[0019] The cast aluminum alloy of the present disclosure may be any Al-Mg cast alloy suitable for casting operations, hi one embodiment, the cast aluminum alloy of the present disclosure may be a 5xx.x aluminum alloy.

[0020] In some embodiments, Ca is present in the cast aluminum alloy at about 0.003 weight percent or more. In some embodiments, Ca is present in the cast aluminum alloy at about 0.01 weight percent or more. In some embodiments, Ca is present in the cast aluminum alloy at about 0.1 weight percent or more. In additional embodiments, Ca is present in at least about 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 2.0, 3.0, 4.0, 5.0, or more weight percent. If Ca is present in the alloy, it is present at 6.0 weight percent or less. In some embodiments, Ca is present in the alloy in a weight percent of about 6.0, 5.0, 4.0, 3.0, 2.0, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02 or less. In some specific embodiments, Ca is present in the alloy in a weight percent of about 0.01 to about 6.0. In additional embodiments, Ca is present in a weight percent of at least about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or more. In some embodiments, Ca is present in the alloy in a weight percent of about 6.0, 5.0, 4.0, 3.0, 2.0, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2 or less. In some specific embodiments, Ca is present in the alloy in a weight percent of about 0.1 to about 6.0. In still other embodiments, Ca is present in the alloy in a weight percent of at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2 or more. In still further embodiments, Ca is present in the alloy in a weight percent of about 0.3, 0.2, 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02 or less.In yet additional embodiments, Ca is present in the alloy in a weight percent of about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or 0.2 to about 0.3, 0.2, 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, or 0.02, such as from about 0.01 to about 0.3 weight percent. In still other embodiments, Ca is present in the alloy in at least about 0.1, 0.2, or more weight percent. In still further embodiments, Ca is present in the alloy in a weight percent of about 0.3, 0.2, or less. In still additional embodiments, Ca is present in the alloy in a weight percent of about 0.1 or 0.2 to about 0.3 or 0.2, such as from about 0.1 to about 0.3 weight percent.

[0021] In some embodiments, Sr is present in the alloy at a weight percent of about 0.003 or greater. In some embodiments, Sr is present in the alloy at a weight percent of about 0.01 or greater. In some embodiments, Sr is present in the alloy at a weight percent of about 0.1 or greater. In some additional embodiments, Sr is present in at least about 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or more weight percent. If Sr is present in the alloy, it is present in less than or equal to 2.5 weight percent. In some embodiments, Sr is present in the alloy in a weight percent of less than or equal to 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01, 0.009, 0.008, 0.007, 0.006, 0.005, 0.004, or less. In some specific embodiments, Sr is present in the alloy in a weight percent of from about 0.003 to about 2.5. In some additional embodiments, Sr is present in at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or more weight percent.In some embodiments, Sr is present in the alloy in a weight percent of about 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02 or less. In some specific embodiments, Sr is present in the alloy in a weight percent of about 0.01 to about 2.5. In some additional embodiments, Sr is present in a weight percent of at least about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or more. In some embodiments, Sr is present in the alloy in a weight percent of no more than about 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, or less. In some specific embodiments, Sr is present in the alloy at about 0.1 to about 2.5 weight percent. In still other embodiments, Sr is present in the alloy at at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or 0.2 weight percent. In still further embodiments, Sr is present in the alloy at no more than about 0.3, 0.2, 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, or less weight percent. In yet additional embodiments, Sr is present in the alloy in a weight percent of from about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or 0.2 to about 0.3, 0.2, 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, or 0.02, such as from about 0.01 to about 0.3. Sr is present in the alloy in a weight percent of at least about 0.1, 0.2, or more.In still further embodiments, Sr is present in the alloy in a weight percent of about 0.3, 0.2 or less, hi yet additional embodiments, Sr is present in the alloy in a weight percent of from 0.1 or 0.2 to about 0.3 or 0.2, such as from about 0.1 to about 0.3 weight percent.

[0022] The cast aluminum alloys of the present disclosure include Mg to provide acceptable mechanical properties to the resulting cast product. Since the primary strengthening mechanism of Mg is solid solution strengthening, adding Mg beyond its solubility in aluminum does not further increase the mechanical properties of the corresponding aluminum cast product. For this reason, the cast aluminum alloys of the present disclosure provide Mg at weight percent up to 17.0. Mg is present in the alloy at at least about 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0, or more. Mg is present in the alloy in a weight percent of less than or equal to about 17.0, 16.0, 15.0, 14.0, 13.0, 12.0, 11.0, 10.0, 9.0, 8.0, 7.0, 6.0, 5.0, 4.0, 3.0, 2.0, or less. In one embodiment, Mg is present in the alloy in weight percent from about 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0 to about 17.0, 16.0, 15.0, 14.0, 13.0, 12.0, 11.0, 10.0, 9.0, 8.0, 7.0, 6.0, 5.0, 4.0, 3.0, 2.0, such as from about 1.0 to 17.0. In some embodiments, Mg is present in the alloy in weight percent of at least about 3.0, 4.0, 5.0, 6.0, 7.0, or more. In some embodiments, Mg is present in the alloy in a weight percent of about 8.0, 7.0, 6.0, 5.0, 4.0 or less. In one embodiment, Mg is present in the alloy in a weight percent of about 3.0, 4.0, 5.0, 6.0, 7.0 to about 8.0, 7.0, 6.0, 5.0, 4.0, such as from about 3.0 to 8.0. In some embodiments, Mg is present in the alloy in a weight percent of at least about 4.0, 5.0, or more. In some embodiments, Mg is present in the alloy in a weight percent of about 6.0, 5.0 or less. In one embodiment, Mg is present in the alloy in a weight percent of about 4.0, 5.0 to about 6.0, 5.0, such as from about 4.0 to 6.0.

[0023] The cast aluminum alloys of the present disclosure include Fe to provide die seizure resistance during casting operations. However, the amount of Fe present in the cast alloys of the present disclosure should be limited to avoid the formation of large iron phases that may be brittle and reduce the mechanical properties of the corresponding aluminum alloy products. Thus, Fe is present in the alloy in a weight percent of at least about 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, or more. Fe is present in the alloy in a weight percent of no more than about 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, or less. In one embodiment, Fe is present in the alloy in a weight percent of about 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 to about 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, such as from about 0.5 to 1.8. In one embodiment, Fe is present in the alloy in a weight percent of at least about 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, or more. Fe is present in the alloy in a weight percent of about 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, or less. In one embodiment, Fe is present in the alloy in a weight percent from about 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 to about 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, such as from about 0.8 to 1.8.

[0024] If desired, a grain refiner may be included in the aluminum alloy of the present disclosure in the form of Ti, TiB2, TiB, or TiC to solidify the aluminum alloy with a fine grain structure that is perfectly equiaxed. When TiB is used as the grain refiner, the resulting B content in the alloy may be up to 0.05 wt.%. When TiC is used as the grain refiner, the resulting C content in the alloy may be up to 0.01 wt.%. The grain refiner may be added during the production of the ingot to be remelted, or it may be added after remelting during the production of the final casting.

[0025] The casting alloys of the present disclosure do not contain Be, either as an intentional additive or as an alloying element. If present, Be is considered to be an unavoidable impurity. In some embodiments of the present disclosure, the cast alloy does not contain Cu, either as an intentional additive or as an alloying element, and thus, in some embodiments, Cu, if present, may be considered an unavoidable impurity.

[0026] The balance of the aluminum alloy of the present disclosure is aluminum (Al) and incidental impurities. In one embodiment, each of the impurities is present in a maximum of about 0.05 weight percent, with the total incidental impurities being present in a weight percent of less than about 0.15 (weight percent).

[0027] The cast aluminum alloys of the present disclosure may be subjected to various casting operations, including but not limited to high pressure vacuum die casting (HPVDC), to obtain aluminum cast products. The presence of Ca or Sr may, in some embodiments, improve casting operations by reducing the amount of Mg loss and / or dross formation during holding of the molten aluminum alloy. In some embodiments, the presence of Ca or Sr may reduce Mg loss during melting to less than about 12 weight percent when the molten alloy is held for at least 6 hours (compared to the corresponding base alloys - Ca, Sr, and / or a combination of Ca and Sr). In some embodiments, the presence of Ca or Sr may reduce dross formation to less than about 7 weight percent when the molten alloy is held for at least 6 hours (compared to the corresponding base alloys without Ca and Sr).

[0028] The present disclosure thus provides methods of producing aluminum cast products from the cast aluminum alloys described herein. The methods broadly involve casting the cast aluminum alloys described herein in a mold, and optionally subjecting the cast aluminum alloy to high pressure vacuum die casting (HPVDC). In some embodiments, the methods avoid the use of a post-casting heat treatment step. In such embodiments, the corresponding aluminum products are provided in the as-cast condition (e.g., temper F).

[0029] In some embodiments of the method, the cast aluminum alloy, which may be provided in the form of an ingot, is subjected to a melting step to obtain a molten aluminum alloy. The melting step includes heating and stirring the aluminum alloy, and optionally holding the molten aluminum alloy before casting. If dross is generated during the melting step (e.g., during the holding step), the method may include removing the dross before casting. Once the molten aluminum alloy is obtained, it is cast in a mold to obtain an aluminum cast product. The casting step may include subjecting the cast aluminum alloy to a high pressure vacuum die casting step. In some embodiments, the method may include removing the aluminum cast product from the mold. In some embodiments, the method of producing an aluminum cast product does not include a post-casting heat treatment step, and the aluminum cast product is obtained in the as-cast state (e.g., temper F). However, in some embodiments, the method of producing cast aluminum may include one or more post-casting treatment steps (e.g., annealing, strain hardening, solution heat treatment, and / or heat treatment).

[0030] In embodiments where the aluminum product is a cast product, the method may also exclude any post-casting treatment (e.g., it may be provided as-cast or as temper F). Alternatively, the method may include a post-casting heat treatment, such as, for example, a T5, T6, or T7 treatment (e.g., a solution heat treatment step and an artificial ageing step). In embodiments where the aluminum product is a cast product, the latter may be an automotive part, such as a chassis or rotor.

[0031] In some embodiments, the casting alloys of the present disclosure can be used to reduce dross formation during casting operations, hi some embodiments, the casting alloys of the present disclosure reduce the weight percent of dross generated during the melting process (e.g., during the holding step) to less than 7, 6, 5, 4, 3, 2, 1% when the molten aluminum alloy is held for at least 6 hours.

[0032] In some embodiments, the casting alloys of the present disclosure can be used to reduce Mg loss during casting operations, hi some embodiments, the casting alloys of the present disclosure reduce the weight percent of Mg loss during the melting process (e.g., during the holding step) to less than 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2% when the molten aluminum alloy is held for at least 6 hours.

[0033] In some embodiments, the method of the present disclosure may include adding Ca or Sr to aluminum or the first aluminum alloy to obtain a master alloy or the casting alloy of the present disclosure. In some embodiments, Ca or Sr is added to pure aluminum to obtain a master alloy. In such embodiments, the master alloy may then be used to produce the casting alloy of the present disclosure, and Mg, Fe, and optionally a grain refiner may be added. The pure aluminum or master alloy does not include Be as an alloying element, and if Be is present, it is considered an impurity. In some embodiments, Ca or Sr is added to a first aluminum alloy that includes Mg and Fe, and optionally a grain refiner, with the balance being aluminum and unavoidable impurities. The first aluminum alloy does not include Be as an alloying element, and if Be is present in the first aluminum alloy, it is considered an impurity.

[0034] The present disclosure also provides aluminum cast products that can be obtained or obtained by the methods described herein. In the context of the present disclosure, the term "aluminum cast product" can refer to a final cast product (e.g., structural automotive parts, etc.) or an intermediate ingot that can be further remelted into aluminum products of different shapes. In some embodiments, the aluminum cast product is a shock tower, an A-pillar, a B-pillar, or a torque box. In some embodiments, the aluminum cast products of the present disclosure exhibit improved tensile strength, yield strength, quality index, VDA angle, and / or percent elongation when compared to the properties of a corresponding aluminum product that does not contain Ca or Sr (and optionally contains Be). In some embodiments, the improved tensile strength, yield strength, quality index, VDA angle, and / or percent elongation is found in the as-cast state (e.g., temper F) of the aluminum product.

[0035] In some embodiments, aluminum cast products produced from the casting alloys of the present disclosure have a tensile strength of at least about 200, 210, 220, 230, 240, 250 MPa, or more. In specific embodiments, aluminum cast products produced from the casting alloys of the present disclosure have a tensile strength of at least about 200 MPa. In some additional embodiments, aluminum cast products produced from the casting alloys of the present disclosure have a yield strength of at least about 100, 110, 120, 130, 140, 150 MPa, or more. In some additional embodiments, aluminum cast products produced from the casting alloys of the present disclosure have a yield strength of at least about 100 MPa. In some additional embodiments, aluminum cast products produced from the casting alloys of the present disclosure have an elongation of at least about 7, 8, 9, 10%, or more. In some additional embodiments, aluminum cast products produced from the casting alloys of the present disclosure have an elongation of at least about 7%. In some additional embodiments, aluminum cast products produced from the casting alloys of the present disclosure meet the angle of standard VDA (Verband der Automobilindustrie) 238-100 of at least about 30° or greater.

[0036] The present invention will be more readily understood by reference to the following examples, which are given to illustrate the present invention and not to limit its scope. Working Example The present examples present the development of a novel aluminum alloy to provide exceptional mechanical properties and die-stick resistance for aluminum HPVDC structural components in as-cast temper applications. The microstructural evolution and mechanical properties were examined by scanning electron microscopy and tensile / bending tests. The relationship between microstructure and properties is analyzed, and the strengthening mechanism of the tested alloy is discussed. Based on the experimental results, the novel alloy demonstrates a promising solution for the as-cast application of HPVDC components.

[0037] As possible substitutes for Be, Ca and Sr were investigated for their effects on preventing the oxidation of liquid Al-1.5Fe-5Mg alloy through the observation and measurement of oxidation morphology, dross formation, and magnesium loss.

[0038] Molten Al-5Mg oxidation tests. Various additions of Ca and Sr in Al-1.5Fe-5Mg alloys were tested. The alloys were produced using P1020 aluminum, pure magnesium, and pure iron powders. The elements of Sr and Ca were batched using master alloys of Al-10%Sr and Al-10%Ca. The chemical compositions of these alloys were analyzed by optical emission spectroscopy (OES) and the results are shown in Table 1. The alloys were melted in the laboratory using a 350-kg electric resistance furnace.

[0039] [Table 1]

[0040] The experimental procedure is presented in Figure 1. The procedure includes two steps: alloy batching process and holding process. A typical alloy batching process was used. More specifically, P1020 was charged into the furnace and batched with Fe and Mg. The molten metal was then stirred and degassed with argon. Flux salts were used to purify the melt during degassing. After degassing, Ca and Sr were added in the proportions of 100 ppm to 0.3% for Ca and 100 to 1000 ppm for Sr according to the chemical design in Table 1. An interrupted thermal holding process was used to investigate the occurrence of oxidation during casting. The metal holding temperature was set at 770°C, which is the upper limit in typical casting. Since the mass of oxides formed on the liquid metal increases with temperature, this test illustrates the effect of Ca and Sr on Al-Mg oxidation under the most severe oxidation conditions. As shown in Figure 1, alloying was followed by three holding times of 2 hours each. After each time period, the appearance of the molten metal surface was photographed. A thorough skimming of the metal surface was performed to quantify the amount of dross formation. Six OES samples were taken to evaluate magnesium loss. The crucible was thoroughly cleaned after each test. For the base Al-1.5Fe-5Mg alloy, longer thermal hold times up to 20 hours were performed to test for oxidation changes.

[0041] Properties and microstructural analysis of Al-Mg alloys. The effect of small amounts of Ca on the mechanical properties and bending ductility of Al-1.5Fe-5Mg alloys was studied. Plates with a thickness of 3 mm obtained by high pressure vacuum die casting (HPVDC) were produced on a 260 ton Buhler machine. The Al-1.5Fe-5Mg base alloy and the new Al-1.5Fe-5Fe0.1Ca alloy were cast. The chemical composition of the investigated alloys was characterized using optical emission spectroscopy (OES) and the results are shown in Table 2.

[0042] [Table 2]

[0043] Samples for tensile testing were cut from the cast blanks (rectangular area in the middle of the sample as shown in Figure 2). The plates were then machined to the shape of the test samples with precise dimensions according to the ASTM B557 standard. Tensile tests were performed on 10 tensile samples in the as-cast condition for each alloy. For bending tests, 60x60 mm square samples were machined from 3 mm HPVDC plates. Six samples for each alloy were tested according to the VDA 238-100 standard.

[0044] Metallographic samples were taken from the as-cast HPVDC plates. Optical and Scanning Electron Microscopy (SEM) were used to analyze the as-cast microstructure and to identify intermetallic phases.

[0045] Effect of Ca and Sr on the oxidation prevention of molten Al-Mg alloy. In order to understand the oxidation mechanism, the oxidation phenomenon of Al-Mg was examined. The effect of Ca and Sr on the oxidation prevention effect of Al-Mg alloy was investigated.

[0046] Oxidation properties of base Al-1.5Fe-5Mg alloy. Figure 3 shows the melt surface of Al-1.5Fe-5Mg alloy during the heat hold at 770°C in air. The melt surface after sufficient skimming is very clean. After 1 hour of exposure, the surface shows partial popcorn-shaped oxidation near the crucible edge. After 2 hours of exposure, the melt surface is completely covered with popcorn-shaped oxide. The temperature of the metal increases to 800°C due to the exothermic oxidation reaction of aluminum and magnesium. After 20 hours of exposure, the color of the oxide turns partially black. The solid popcorn-shaped oxide has a porous morphology, as shown in Figure 4A, which consists of numerous pores and oxide clusters (see Figure 4B). EDX analysis shows that the dross is mainly composed of magnesium oxide (MgO) and spinel (MgAl2O4).

[0047] Figures 5A and 5B show the change in Mg concentration from 0 to 6 hours of holding time, as well as the percentage of Mg loss after a total holding time of 6 hours. It can be seen that the base Al-1.5Fe-5Mg alloy experienced the highest Mg loss. The total Mg loss after a holding time of 6 hours is 0.63 wt% or 12.6% loss. The addition of Ca or Sr effectively reduced the Mg loss during melting. The Mg loss was less than 0.1 wt% or 2% loss for the Ca-containing alloys, and less than 0.3 wt% or 6% loss for the Sr-containing alloys.

[0048] Combination of Ca and Sr. Figure 6 shows the visual appearance of molten Al-1.5Fe-5Mg based alloys with no additives, only Ca, only Sr, and combination of Ca and Sr. The alloy containing both Ca and Sr has small wavy shape. This feature is similar to that of the Sr-containing alloy. The oxide layer appears to be thick. No porous dross is present. This result indicates that the combination of Ca and Sr can help effectively combat the oxidation of Al-1.5Fe-5Mg.

[0049] Figure 7 shows the total amount of dross generated (wt% of input) after a total holding time of 6 hours. It is noted that the combination of Ca and Sr effectively reduced dross formation. The alloy containing both Ca and Sr showed 2.1 wt% dross formation, which is lower than the dross formation of the base alloy (6.9 wt%) and the alloy containing Sr (2.9 wt%). However, the amount of dross generated is higher than the amount of dross of the alloy containing Ca (1.0 wt%).

[0050] In summary, Mg in Al-1.5Fe-5Mg has a strong affinity for oxygen. In the case of the base alloy, a thick oxide was observed on the melt surface. Both Ca and Sr showed good effects in preventing the oxidation of Al-1.5Fe-5Mg.

[0051] Mechanical properties. The properties of Al-1.5Fe-5Mg and Al-1.5Fe-5Mg0.1Ca were tested. Table 3 summarizes the tensile properties and VDA bend results for the as-cast test and reference alloys. Figure 8 shows the effect of Ca on the mechanical properties of Al-1.5Fe-5Mg alloy. It was found that Al-1.5Fe-5Mg0.1Ca exhibits superior tensile properties compared to Al-1.5Fe-5Mg alloy. Both tensile strength and ductility are higher for Al-1.5Fe-5Mg0.1Ca alloy than Al-1.5Fe-5Mg alloy. QI=UTS+150 * The alloy quality index (QI), calculated using the formula log(El%), is 459 MPa for Al-1.5Fe-5Mg0.1Ca, which is 81 MPa or 21% higher than Al-1.5Fe-5Mg. Meanwhile, as shown in Table 3, the Al-1.5Fe-5Mg0.1Ca alloy gives better bending ductility than the Al-1.5Fe-5Mg alloy (bending angle 37.7° for Al-1.5Fe-5Mg0.1Ca vs. 29.0° for Al-1.5Fe-5Mg alloy). The results highlight the beneficial effect of Ca on the mechanical performance of the Al-1.5Fe-5Mg0.1Ca alloy.

[0052] [Table 3]

[0053] Figure 9 shows the mechanical properties of the new Al-1.5Fe-5Mg0.1Ca alloy in comparison with other commercially available die casting alloys (e.g., Comparative Alloys 1 and 2). The new alloy showed higher quality index values ​​than Comparative Alloys 1 and 2. It had the highest overall tensile strength and yield strength.

[0054] Compared to Comparative Alloy 1, which contains 7.5 wt% Si and 0.17 wt% Fe, the Al-1.5Fe-5Mg0.1Ca alloy had higher tensile strength and lower elongation. The elongation was 11.5% for Comparative Alloy 1 compared to 10% for the Al-1.5Fe-5Mg0.1Ca alloy. Interestingly, the Al-1.5Fe-5Mg0.1Ca alloy showed better bending ductility than Comparative Alloy 1, with a bending angle of 37.7° for the Al-1.5Fe-5Mg0.1Ca alloy compared to 32.4° for the Comparative Alloy 1. It is believed that the Al-1.5Fe-5Mg0.1Ca alloy has similar or better ductility than Comparative Alloy 1. With regard to die seizure resistance, the Al-1.5Fe-5Mg0.1Ca alloy contains 1.5 wt% Fe, which is believed to reduce the tendency to stick and significantly improve the die life compared to Comparative Alloy 1.

[0055] Compared with the comparative alloy 2, Al-1.6Fe-4.2Mg-Be alloy, the Al-1.5Fe-5Mg0.1Ca alloy showed higher strength but lower ductility. Without being bound by theory, this may be due to the higher Mg content in the Al-1.5Fe-5Mg0.1Ca alloy (5.1 wt.% Mg) than the comparative alloy 2 (4.3 wt.% Mg), which provided a higher solid solution strengthening effect. The ductility of the Al-1.5Fe-5Mg0.1Ca alloy can be improved by decreasing the amount of Mg when higher elongation is required. In terms of the alloy quality index, the Al-1.5Fe-5Mg0.1Ca alloy showed a higher quality index value (459 MPa) than the comparative alloy 2 (427 MPa). The Al-1.5Fe-5Mg0.1Ca alloy had better mechanical properties overall than the comparative alloy 2. With regard to die seizure resistance, the Al-1.5Fe-5Mg0.1Ca alloy and Comparative Alloy 2 had similar Fe contents of 1.5 wt% versus 1.6 wt%. The Al-1.5Fe-5Mg0.1Ca alloy is expected to perform similarly to the Comparative Alloy with regard to die life.

[0056] As-cast microstructural analysis. To understand the strengthening mechanism of Ca in Al-1.5Fe-5Mg alloy, microstructural analysis was performed on the as-cast plates. The results are shown in Table 10. Al-1.5Fe-5Mg shows shrinkage porosity, while Al-1.5Fe-5Mg0.1Ca shows a pore-free microstructure. Since Ca is very efficient in reducing Al-Mg oxidation, it makes sense that Al-1.5Fe-5Mg0.1Ca has fewer oxides and lower porosity.

[0057] The morphology and chemistry of the phases were identified using SEM / EDX and EBSD analysis. The results are shown in Figure 11. Table 4 summarizes the different stable phases identified in the two alloys tested. The alloy matrix is ​​mainly Al in the Al-1.5Fe-5Mg alloy. 13 Fe4 and Al3Mg2 phases, Al-1.5Fe-5Mg0.1Ca alloy with Al 13 The microstructure of the Al-1.5Fe-5Mg0.1Ca alloy consisted of Fe4 and Al3Mg2 / Al4Ca phases. The addition of Ca to the Al-5Mg-1.5Fe alloy allows the formation of Al4Ca or AlMgCa phases joined with the Al3Mg2 phase at the grain boundaries in the matrix. In addition, Ca appears to slightly modify the morphology of the iron-rich phase. It was observed that there were more partially fragmented script Fe phases distributed very non-uniformly in the microstructure of the Al-1.5Fe-5Mg0.1Ca alloy. The small grains promote uniform deformation and result in higher elongation in the tensile test.

[0058] [Table 4]

[0059] Additionally, the effect of Mg addition on the mechanical properties of the alloy was also examined. Essentially, the tensile strength (UTS) and yield strength (YS) increased with increasing Mg content, as seen in Table 5 below and Figure 12.

[0060] [Table 5]

[0061] Although the present invention has been described in connection with specific embodiments thereof, it will be understood that the scope of the claims should not be limited by the preferred embodiments set forth in the examples, but should be accorded the broadest interpretation consistent with the entire description.

Claims

1. In weight percent, from about 1.0 to about 17.0 Mg; Fe from about 0.5 to about 1.8; one of about 0.003 to about 6.0 Ca or about 0.003 to about 2.5 Sr; and Residual amounts of aluminum and unavoidable impurities, and does not contain Be as an alloying element.

2. The casting alloy of claim 1 further comprising a grain refiner.

3. 3. The casting alloy of claim 1 or 2, further comprising Ca.

4. 3. The casting alloy of claim 1 or 2, comprising from about 0.01 to about 0.3 Ca.

5. 3. The casting alloy of claim 1 or 2, comprising from about 3.0 to about 8.0% Mg.

6. 3. The casting alloy of claim 1 or 2, comprising about 4.0 to about 6.0 Mg.

7. 3. The casting alloy of claim 1 or 2, comprising from about 0.8 to about 1.8 Fe.

8. 13. An aluminum cast product comprising the casting alloy of claim 1.

9. 3. A method for producing an aluminium cast product, comprising casting the casting alloy of claim 1 or 2 in a mould.

10. 10. The method of claim 9, further comprising subjecting the cast aluminum alloy to high pressure vacuum die casting.

11. 10. The method of claim 9, which does not include a post-casting heat treatment step.

12. 10. An aluminium cast product obtainable or obtained by the method according to claim 9.

13. 13. The aluminum cast product of claim 8 or 12 which is a structural automotive part.

14. At least one of the following characteristics: - a tensile strength of at least about 200 MPa; a yield strength of at least about 100 MPa, - an elongation of at least about 7%, and - a VDA bending angle of at least about 30°, 13. The aluminum casting product according to claim 8 or 12, having

15. A 4 The aluminum casting product according to claim 8 or 12, further comprising Ca.

16. A 13 Fe 4 Phase, Al 3 Mg 2 phase, and Al 4 13. The aluminum casting product according to claim 8 or 12, having a Ca phase.

17. The Al 3 Mg 2 Al bonded with phase 4 The aluminum cast product according to claim 16, comprising Ca.

18. 13. An aluminium cast product according to claim 8 or 12, having an AlMgCa phase at the grain boundaries.

19. 1. A method of limiting Mg loss and dross formation during a casting operation of an aluminum product compared to a control aluminum product, comprising adding, in weight percent, one of about 0.003 to about 6.0 Ca or about 0.003 to about 2.5 Sr to a first aluminum alloy to obtain a casting alloy intended to be cast, said first aluminum alloy having, in weight percent: from about 1.0 to about 17.0 Mg; Fe from about 0.5 to about 1.8, and Residual amounts of aluminum and unavoidable impurities, wherein the first aluminum alloy and the cast alloy do not include Be as an alloying element.

20. 20. The method of claim 19, wherein the first aluminum alloy further comprises a grain refiner.

21. 21. The method of claim 19 or 20, further comprising melting the casting alloy to obtain a molten casting alloy.

22. 22. The method of claim 21, for reducing Mg loss to less than about 12 weight percent when the molten cast alloy is held for at least 6 hours.

23. 22. The method of claim 21, for reducing dross formation to less than about 7 weight percent when the molten cast alloy is held for at least 6 hours.

24. 22. The method of claim 21, further comprising casting the molten casting alloy to obtain a cast aluminum alloy.

25. 25. The method of claim 24, further comprising subjecting the cast aluminum alloy to high pressure vacuum die casting.

26. 21. The method of claim 19 or 20, which does not include a post-casting heat treatment step.

27. 21. The method of claim 19 or 20, wherein the cast aluminum alloy comprises Ca.

28. 28. The method of claim 27, wherein the cast aluminum alloy comprises about 0.01 to about 0.3 Ca.

29. 21. The method of claim 19 or 20, wherein the first aluminum alloy comprises from about 3.0 to about 8.0 Mg.

30. 21. The method of claim 19 or 20, wherein the first aluminum alloy comprises from about 4.0 to about 6.0 Mg.

31. 21. The method of claim 19 or 20, wherein the first aluminum alloy comprises from about 0.8 to about 1.8 Fe.